Identification of primary metabolite of tomato grown in different parts of Meghalaya, India (International Journal of Food and Nutritional Sciences, 2022)
The state of Meghalaya is well-known for both its horticulture crop types and tourism. One of the major crops that is grown all year round in Meghalaya is the tomato. Metabolites are used to assess the quality of tomatoes from various regions in Meghalaya. LCMS spectroscopy was used to discover primary metabolites in eleven tomato genotypes from various regions of Meghalaya. Primary health-promoting metabolites were present in all genotypes that were analyzed; however, the round-shaped tomato from Baghmara, which measured 4.9 cm in diameter, and the egg-shaped tomato from Resubelpara, which had an average diameter of 4.4 cm, were found to be a rich source of these metabolites, whereas the genotypes collected from Tura, Jowai, Nongpoh, and Mawkyrwat had the fewest number of primary metabolites. Given the reported differences in metabolite composition, it may be possible to use breeding techniques and genotypic selection to improve particular health-promoting traits in tomatoes.